Sara E. Ellis Nilsson, Creating Holy People and Places on the Periphery. A Study of the Emergence of Cults of Native Saints in the Ecclesiastical Provinces of Lund and Uppsala from the Eleventh to the Thirteenth Centuries - Salonen, Kirsi (Journal of Northern Studies, 2016)
Review of: Sara E. Ellis Nilsson, Creating Holy People and Places on the Periphery. A Study of the Emergence of Cults of Native Saints in the Ecclesiastical Provinces of Lund and Uppsala from the Eleventh to the Thirteenth Centuries, Gothenburg: University of Gothenburg 2015, ISBN 9789162892746, 372 pp.